A WEBGIS FOR DATA COLLECTION AND DECISION SUPPORT IN NATURAL DISASTER MANAGEMENT: A CASE OF BAMENDA, CAMEROON - Akam, B.; Zhang, F.; Laari, P. B. (UDS International Journal of Development, 2019)
WebGIS is increasingly becoming a useful spatial tool for effective interventions and decision-making in disaster and natural resource management. This paper presents the techniques used for the development of a prototype Web based GIS tool for risk analysis of natural hazards like floods and landslides. The scheme designed uses open source as well as proprietary geospatial software and technology. It aims at being a prototype or a tool to assist officials and risk managers in analyzing the vulnerability of communities to identify risk. Moreover, it also serves as a useful data collection mechanism, place of identification and interactive visualization tool. This is a vital input into the decision-making process to enable risk managers make informed decisions in the selection of natural hazard management strategies. The platform developed enables users to upload information about recent hazard occurrences, do flood plain delineation, and interactively visualize datasets of the area of study. This system basically combines hazard history, recent hazard occurrence, hydrological and landscape information for natural hazard monitoring. It is expected that this would serve as a base tool to spatially monitor, highlight and tailor interventions at areas prone to natural disaster occurrence. Keywords: WebGIS, Risk Assessment, Flood and Natural Disaster